Peran Penting Komunikasi Pemasaran dalam Mewujudkan Usaha yang Mandiri bagi para Pelaku UMKM di Wilayah Kotabaru - Khuzaini Khuzaini; Junaidi Junaidi; Noorlaily Maulida; Ilisa Fajriyati; Sanusi Sanusi; M. Haris Syafitri (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
Micro, Small, and Medium Enterprises (MSMEs) have a very important role in the local and national economy, especially in the Kotabaru area. MSMEs play a role in absorbing labor, overcoming poverty, and distributing development results. MSMEs usually produce on a small scale and require attention in marketing the products they produce. Marketing communication can be a strategy for every MSME to learn to introduce the products they produce to other parties or the general public so that they have the same understanding and intention of the products and brands being sold. Every MSME, in addition to focusing on producing competitive products, must also be able to market what they produce. In the early stages, every MSME must be able to read market needs, so that they can produce products according to the targeted market segment. Furthermore, MSMEs can use the communication facilities they have and join MSME centers according to the type of business they have. By using good marketing communication, it will have an impact on the progress of the business being carried out and MSMEs will grow into competitive MSMEs